Efektivitas pakan moist berbasis singkong dan keong pada budidaya lobster air tawar (Cherax quadricarinatus) - Novita MZ; Neneng Nurbaeti; Saepul Miptah; Damar Maulana Yahya; Gilang Ramadhan (JURNAL PERIKANAN DAN KELAUTAN, 2023)
The feed plays a critical role in the success of freshwater lobster cultivation, but it often presents challenges due to its relatively high cost, accounting for up to 60% of production expenses. To address this issue, farmers in Sukabumi have devised various alternative feeds by harnessing different protein sources to reduce the expenditure on commercial pellets. One such innovation is a moist feed composed of a blend of pellets, cassava, and snails in a ratio of 1:1:1.4. However, there hasn't been prior testing of its nutritional content. Consequently, this study aims to evaluate the nutritional composition of this moist feed and assess its impact on the growth of freshwater lobsters as well as water quality. For this research, a total of 300 lobsters, ranging in size from 7 to 10 grams, were reared in fiberglass tanks. The lobsters were fed twice daily. The proximate analysis of the cassava and snail-based moist feed revealed protein content (20.52%), fat (2.61%), carbohydrates (12.87%), moisture content (50.64%), and ash content (13.36%). The lobsters exhibited a growth rate of 0.3% per day, and the water quality remained favorable, with parameters such as temperature (23-25°C), pH (6.5-7), dissolved oxygen (5-7 mg/L), nitrate (1.907 mg/L), nitrite (0.141 mg/L), ammonia (0.442 mg/L), phosphate (0.032 mg/L), and alkalinity (237.4 mg CaCO3/L) within acceptable ranges. These findings suggest that the moist feed provided by farmers lacks sufficient protein content to fully meet the nutritional requirements of lobsters, resulting in slower growth. On the other hand, water quality remains conducive for successful lobster farming.